2020
DOI: 10.24251/hicss.2020.428
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of a Telemedicine-based Substance Use Disorder Evaluation to Enhance Access to Treatment Following Near-Fatal Opioid Overdose

Abstract: The opioid epidemic is a growing public health emergency in the United States, with deaths from opioid overdose having increased five-fold since 1999. Emergency departments (EDs) are the primary sites of medical care after near-fatal opioid overdose but are poorly equipped to provide adequate substance use treatment planning prior to discharge. In many underserved locales, limited access to clinicians trained in addiction medicine and behavioral health exacerbates this disparity. In an effort to improve postov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They range from Internet-based standalone interventions to newer forms of interventions that combine the strengths of face-to-face and Internet approaches, blended interventions. Great numbers of e-health interventions have been found effective in improving health-related outcomes over a great variety of target conditions and patient groups, both with regard to medical and mental health, in adults and adolescents (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Several studies have identified facilitators and barriers in the implementation and sustainability of e-health interventions (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…They range from Internet-based standalone interventions to newer forms of interventions that combine the strengths of face-to-face and Internet approaches, blended interventions. Great numbers of e-health interventions have been found effective in improving health-related outcomes over a great variety of target conditions and patient groups, both with regard to medical and mental health, in adults and adolescents (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Several studies have identified facilitators and barriers in the implementation and sustainability of e-health interventions (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…One method of dealing with the challenge is to refer to telemedicine-based addiction services. A pilot study showed telemedicine-based referral and access to addiction treatment following non-fatal opioid overdose-related emergency department admission is a promising option (47). Despite the interest in the implementation of telemedicine-based addiction treatment costs associated with implementation, lack of reimbursement for telemedicine services, providers' unfamiliarity with technology, lack of implementation models, and confidentiality regulations were reported as important barriers (48).…”
Section: Challenges Of Expanding and Implementing Screening And Briefmentioning
confidence: 99%
“…The evidence suggests that the results obtained through this modality are comparable with the services offered in an in-person appointment (Osenbach et al, 2013), they present drop-out rates similar to the face-to-face modality and acceptable levels of satisfaction (Chipps et al, 2020). Some of the ways in which telehealth has been used in ambulatory treatment centers are through detection and treatment programs based on computing equipment, phone apps, phone therapy and, recently, through clinical videoconferences (Fisher et al, 2021;Lai et al, 2020). The term "clinical videoconference" refers to an active videoconference held between a health service provider and a patient, with purposes that range between brief interventions to providing prescriptions and the management of medication (Lustgarten et al, 2020).…”
mentioning
confidence: 96%